2014
DOI: 10.1617/s11527-014-0431-3
|View full text |Cite
|
Sign up to set email alerts
|

Determination of particle size, surface area, and shape of supplementary cementitious materials by different techniques

Abstract: The particle size distribution, surface area and shape are fundamental characteristics of supplementary cementitious materials (SCMs). Accurate measurement of these properties is required in computational efforts to model the hydration process, and the characterization of these parameters is also an important practical issue during the production and use of blended cements. Since there are no standard procedures specifically for the determination of physical properties of SCMs, the techniques that are currentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(44 citation statements)
references
References 12 publications
1
41
0
2
Order By: Relevance
“…The surface areas measured for the calcium-aluminosilicate powders an order of magnitude higher than those typically observed for ground granulated blast furnace slag (typically 0.2 -0.8 m 2 /g) [11,35], while the pore size distribution data for all calcium-aluminosilicate powders indicate a distribution of pore sizes centred at approximately 60 -70 nm for low-Ca samples C and E, and 20 -50 nm for highCa samples D and F.…”
Section: Chemical and Physical Characterisation Of Powdersmentioning
confidence: 99%
“…The surface areas measured for the calcium-aluminosilicate powders an order of magnitude higher than those typically observed for ground granulated blast furnace slag (typically 0.2 -0.8 m 2 /g) [11,35], while the pore size distribution data for all calcium-aluminosilicate powders indicate a distribution of pore sizes centred at approximately 60 -70 nm for low-Ca samples C and E, and 20 -50 nm for highCa samples D and F.…”
Section: Chemical and Physical Characterisation Of Powdersmentioning
confidence: 99%
“…The high SEP carbonate content (calcite and dolomite) presented [50]. BET is known to be more influenced than the air-permeability methodology by surface roughness, open porosity and micro-cracks [11,51]. Considering helium pycnometry density value, it can be observed that SEP is denser than STA.…”
Section: Sediment Characteristics and Discussionmentioning
confidence: 96%
“…First, the main geometric characteristics of the layer and particles were evaluated. Important characteristics of the layer of granular materials that are necessary for calculating thermal characteristics of the heat exchange process and analyzing the results obtained are as follows: porosity ε of the layer and the equivalent particle diameter e d [14]. It was established that the claydite layer porosity ε k =0.47, porosity of the gravel layer ε r =0.5.…”
Section: Characteristics Of Materialsmentioning
confidence: 99%
“…The f i factor which characterizes deviation of the particle shape from spherical shape is equal to one for balls and can be found according to recommendations of [14] for particles of other shapes as follows:…”
Section: Characteristics Of Materialsmentioning
confidence: 99%